Contract For Services For The Billing Of Health And Long-term Care Insurance Services To Other Service Providers And Direct Billers As Well As Related Services [Tender documents : T490074001] (MENA Report, 2023)
Contract notice: contract for services for the billing of health and long-term care insurance services to other service providers and direct billers as well as related services The subject of the procurement project is the award of a contract for billing services for health and long-term care insurance to other service providers and direct billers as well as associated services over a period of three years (basic contract period). on the one hand, the contractor should prepare the billing of the services via software applications in such a way that the administration and processing effort of the client is reduced to a minimum. on the other hand, the contractor should provide a so-called approval tool with which the regulations for home nursing care according to 37 sgb v are prepared and prepared for the decision by the client.The ikk sdwest (client) is a guild health insurance company within the meaning of 4 paragraph 2 sgb v for the federal states of saarland, rhineland-palatinate and hesse. it has a total of 21 locations, around 475,000 members and more than 635,000 insured, whose high-quality care by around 1,500 employees. prescriptions and invoices with a total volume in the nine-digit range are currently issued every year. to increase efficiency, measures for billing prescriptions and invoices to service providers in accordance with 301a, 302 sgb v as well as 105 sgb xi (collectively referred to as other service providers) and directly billing service providers according to 295 para. 1b sgb in conjunction with 140a sgb v (direct billing). the individual service providers are listed in the tender documents. the contractual obligations include: (1) acceptance of all data relevant to the provision of services from the existing contractor (migration); (2) implementation of software-based processes and applications to support dera. billing of health and long-term care insurance services from other service providers and direct billing in the form of billing software in the billing system environment of the client undb. collection, presentation and processing of regulations for home nursing according to 37 sgb v in the form of an approval tool (complete systems), in particular through the implementation of an it interface and training services for the employees of the client; (3) operation of the overall systems mentioned by a. recording, processing, checking and preparing for payment of all invoices, regulations and other documents supporting invoices from other service providers according to 301a sgb v, 302 sgb v, 105 sgb xi and direct billers according to 295 para. 1b sgb v i.V.M. 140a sgb v by means of billing software as well as creation and dispatch of the partial / deductions on behalf and in the name of the client; b. collection, presentation and processing of regulations to prepare a decision by the client in the field of home nursing according to 37 sgbv based on (processing) regulations specified by the Major organization : IKK SDWEST (KRPERSCHAFT DES FFENTLICHEN RECHTS MIT SELBSTVERWALTUNG GEMSS 4 ABS. 1 SGB V) Address : Europaallee 3-4 Country :Germany Email : fsiebler@wfw.com Url : https://www.ikk-suedwest.de/ Tender notice number : 362291-2023 Notice type : T490074001.html © 2022 Al Bawaba (Albawaba.com) Provided by SyndiGate Media Inc. (Syndigate.info).